Satisfaction of academic medical staff with integrated medical curriculum: an exploratory multinational survey - Ghazi F. Sharkas; Ragaa El-Masry; Sameh Abdel-Ghany; Ayman El Baz; Tamer Abou-Elsaad; Amira Adly Kassab; Darwish H. Badran; Abdalla Y. Bashir (BMC Medical Education)
Abstract Background The adoption of integrated curricula in medical schools has grown globally, emphasizing the need to understand academic medical staff satisfaction as a crucial factor influencing successful implementation. Aim This study aimed to assess satisfaction levels among academic medical staff with integrated medical curricula, identifying socio-demographic and work-related predictors of dissatisfaction. Methods A cross-sectional, online multinational survey was conducted from December 2023 to April 2024 among 525 academic medical staff. A structured, self-reported questionnaire was used to assess satisfaction levels, demographic characteristics, and work-related factors. The data were analyzed using descriptive and inferential statistics, including logistic regression analysis, to identify predictors of dissatisfaction. Results The study revealed a low satisfaction rate (44.2%) among medical staff, with significant dissatisfaction influenced by nationality (Jordanian: OR = 7.74, and Egyptian: OR = 4.68), male gender (OR = 3.27), over ten years of teaching experience in integrated curricula (OR = 4.25), and employment in governmental universities (OR = 4.23). Dissatisfaction was particularly high with aspects such as the integration of basic and clinical sciences, assessment methods, and implementation schedules. Faculty from private universities demonstrated significantly higher satisfaction (65.1%) compared to those in governmental institutions (41.3%). Younger staff < 45 years reported higher satisfaction rates (50.9%) compared to their older counterparts ≥ 45 years (39.1%), reflecting greater adaptability to curriculum changes. Conclusions The findings highlight substantial dissatisfaction among academic medical staff with the design and implementation of integrated curricula, particularly in governmental institutions and among senior faculty. Institutions must address challenges in curriculum design, resource allocation, and faculty support to enhance satisfaction. Revisiting conventional curriculum components or adopting a hybrid approach may help balance innovation with faculty preferences, fostering a more conducive educational environment.